Implementation of Baseband Binary Communications over a Distorted Channel - K. Sridar, R. Reshmi, Soumya S. Raj (Mathematical Statistician and Engineering Applications, 2023)
In this work the use of a nulling filter to remove/mitigate the effects of a sinusoidal jamming signal on a baseband digital communications waveform is implemented. The design of the jamming filter itself is the main focus of this work. The use of a nulling or notch filter in the context of a digital communication system might seem too advanced. Details of the digital communication system will be kept to a high level, yet allow some exposure to digital communication concepts. BEP performance using the semi-analytic simulation technique is shown. Results are shown with and without the IIR notch filter. The number of symbols used in the simulation is increased from 1000 to 100,000 to improve the statistical accuracy of the SA-BEP method. At PE = 10-6 we see a performance improvement of about 0.83 dB.